El silencio abyecto en la plaza del diamante - Weng, Miaowei (Boletín Redipe, 2018)
The article examines the gender roles imposed on women in Spain under the Franco regime. It revisits Mercè Rodoreda’s 1962 novel The Time of the Doves and deciphers the female protagonist’s silence in the context of the post-Civil War period. Drawing on Julia Kristeva’s conception of the abject, it explores how silence becomes informative of the protagonist’s mental resistance to the patriarchal imposition, the helplessness and powerlessness a common woman feels under the Franco regime, and the gradual growth of female subjectivity.
Keywords: dept.wll; peer-reviewed; ⛔ No DOI found